INCONSISTENCY IN THE IMPLEMENTATION OF SEMA NO. 4 OF 2014 CONCERNING THE EMPTYING OF MORTGAGE RIGHT AUCTION OBJECTS: ANALYSIS OF COURT DECISIONS AND ITS IMPLICATIONS FOR LEGAL CERTAINTY FOR CREDITORS - Uzie Valerie; Wardani Rizkianti (RADJA PUBLIKA, 2026)
This study examines the inconsistency in the application of Supreme Court Circular (SEMA) Number 4 of 2014 concerning the eviction of mortgage auction objects and its implications for creditor legal certainty. Employing a normative juridical method with statutory and case-based approaches, this research analyzes two court decisions: Palu District Court Decision No. 57/Pdt.G/2023/PN Pal and Klaten District Court Decision No. 93/Pdt.G/2019/PN Kln. The findings reveal that inconsistency manifests in two forms: procedural, where SEMA was entirely unaddressed despite physical eviction having been carried out prior to the verdict; and normative-substantive, where the creditor protection spirit underlying SEMA was ignored in the judges' legal reasoning. Both forms of inconsistency result in illusory legal certainty for creditors, rendering the parate execution right guaranteed under Article 6 of Law Number 4 of 1996 on Mortgage Rights effectively unenforceable in practice.